Dual Track or Academic Route for Auditors: Does It Matter? - Joop Hartog; Nicole Jonker; Hans van Ophem (Institute for the Study of Labor (IZA), 2002)
In the Netherlands auditors can be trained in a part-time educational track in which students combine working and studying or in a full-time educational track. The former training is relatively firm-specific whereas the latter training is relatively general. Applying human capital theory, we expect higher wage growth for full-time educated auditors than for dual-educated auditors. Furthermore, full-time educated auditors may have better outside options than parttime educated auditors. This may make it easier for them to switch employers than for the part-time educated auditors. The predictions on tenure and wages of differently educated auditors are supported by the estimation results in this paper. The part-time, dual track appears an important route for students from lower socioeconomic background.
Keywords: C35; C41; J24; J31; J63; 330; human capital formation; mobility; wages; auditors; Berufsbegleitende Ausbildung; Betriebswirtschaftsstudium; Wirtschaftsprüfung; Bildungsertrag; Vergleich; Schätzung; Niederlande